Eve (mysterium in 3 parts) - Massenet, Jules 1842-1912 (Arte Nova, 1998)
Eve: Mystère en trois parties. Livret: L.Gallet.
Interpr.: Geb, Susanne (Sopr). Kolarczyk, Armin (Bar). Simos, Angelo (Ten). Euregio Symphony Orchestra. Three Nation Choir. Faber, Jeanpierre (Dir.).